Edible coating with Eugenia pyriformis leaf extract to control enzymatic browning in fresh-cut apples (Research, Society and Development, 2020)
Fruits and vegetables are an important part of a healthy and balanced diet. Fresh cut fruits consumption is increasing, however keeping the food quality when processed is a challenge for the food industry. When the food is processed, some enzymatic changes can occur, being that enzymatic browning is one of this important degradation suffered by fresh cut apples. One alternative to reduce the enzymatic browning is the use of edible coating with anti browning components as vegetal extracts rich in phenolic compounds. The aim of this paper was characterize Uvaia (Eugenia pyriformis Cambess) leaf extract, evaluate the effect of sodium alginate edible coating formulated with uvaia leaf extract against enzymatic browning in fresh cut apples (cv. Golden Delicious and Royal Gala) during 8 days of storage. Phenolic compounds as chlorogenic acid, caffeic acid and p-coumaric acid were identified in Uvaia methanolic leaf extract. Uvaia aqueous leaf extract presented ABTS IC50 of 0.77 ± 0.002 mg/mL, increasing 40.66% the edible coating antioxidant activity. Uvaia aqueous leaf extract controlled 80% of polyphenol oxidase activity from Golden Delicious apple and edible coating with extract reduced enzymatic browning. Sodium alginate edible coating with Uvaia aqueous leaf extract is an alternative to reduced enzymatic browning of fresh cut apple (cv. Golden Delicious).